Tsunamis
DOI: 10.1007/1-4020-3331-1_6
|View full text |Cite
|
Sign up to set email alerts
|

Tsunami Resonance Curve from Dominant Periods Observed in Bays of Northeastern Japan

Abstract: Seiche oscillations were observed under quiet sea conditions in 36 bays in the Sanriku district of northeast Japan from September 24, 2001 to August 11, 2002. A semiconductor pressure gauge was installed at quays in heads of bays to detect a water level for 6 hours with a sampling interval of 1 minute. Dominant periods were determined from the maximum levels in the amplitude spectra. The resulting dominant periods varied from 7 to 60 minutes, with an average of 25 minutes. Most of them corresponded to those of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…It was found that the natural modes of the sea areas that extend in front of the bay play an important role in tsunami amplification. In Japan, Abe (2005) calculated the tsunami resonance curve from the dominant periods of bays in the Sanriku region of northeastern Japan and compared them with spectra of near‐field and trans‐Pacific tsunamis. Kim and Jin (2016) studied wave trapping in the Ibaraki Bay of the 2011 Tohoku earthquake.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the natural modes of the sea areas that extend in front of the bay play an important role in tsunami amplification. In Japan, Abe (2005) calculated the tsunami resonance curve from the dominant periods of bays in the Sanriku region of northeastern Japan and compared them with spectra of near‐field and trans‐Pacific tsunamis. Kim and Jin (2016) studied wave trapping in the Ibaraki Bay of the 2011 Tohoku earthquake.…”
Section: Introductionmentioning
confidence: 99%
“…The 6-h PG1 record with 1-min sampling beginning at 00:00 (UTC) of 4 January 2009 was low-pass filtered (Fig. 8b); the PG1 spectrum was constructed in the same way as for the coastal stations (see ABE, 2005a).…”
Section: Resultsmentioning
confidence: 99%
“…For example, the tsunami resonance by the superposition of several oscillation modes in Concepcion Bay and significant tsunami periods of the 1960 and 2010 Chile tsunamis led to the unexpected tsunami inundation and devastation at Talcahuano harbor (Aránguiz, 2015; Aránguiz et al., 2019). It has been demonstrated that the oscillation periods in the bays of the Sanriku region in the northeast Japan coincided with some local and trans‐Pacific tsunami events, which caused severe human casualties and coastal infrastructure damage in the Sanriku (Abe, 2005; Wang et al., 2021).…”
Section: Tsunami Dynamicsmentioning
confidence: 99%